Nos labirintos da lei: a retórica da reforma agrária no Estado democrático de direito brasileiro (1995-2006) - Silva, Jeanne (2010)
Based on the statements of Senators, speeches of Presidents of the Republic (Fernando Henrique Cardoso and Luiz Inacio Lula da Silva) and the volume of legislation (laws and court proceedings), the thesis highlights the complexity of the maze that is the discussion topic of Agrarian Reform in Brazil, from 1995-2006. Rhetoric is one of the tools used by these political agents in order to convince about the importance of the arguments that advocate for Agrarian Reform. The research examines the historical social struggles and the correlation of forces that are present in the process of drafting laws in the content of reading (comprehension - interpretations) and application. Thus, the research analyzes the legislative output of the agrarian period, conceiving the law as an argumentative practice and the construction of laws and their subsequent application as a result of social struggles, showing historically how in practice the "democratic state" "right" has acted in relation to the subject, that is, as the executive, legislature and judiciary, and faced with the organized forum of civil society - the Movement of Struggle for the Land - have been concretely active in the struggles around the land agrarian reform issue.